Using the Movies to Illustrate the Principles of Experimental Design. (April 2018) - Strelan, Peter
This article presents an innovative technique for teaching the principles of experimental design in a way that is entertaining and engaging for students. Following a lecture on experimental design, students participate in an experiment in which the teacher uses a funny segment from a movie to test the influence of implicit social norms. Randomly allocated "participants" receive either laughter cues from the class (experimenter confederates) or no cues. Condition "hilarity" ratings are compared, and the class as a whole discusses issues relating to experimental design including internal validity, random assignment, and independent and dependent variables. Student feedback, including pre- and postactivity ratings, suggests that the exercise may be useful for enhancing students' understanding of experimental design. Most importantly, the exercise provides a fertile context for active learning, and the usefulness of the exercise does not rely on the "success" of the experiment itself.